Primary and secondary psychopathy relate to lower cognitive reappraisal: A meta-analysis of the Dark Triad and emotion regulation processes - Walker, Sarah A.; Olderbak, Sally; Gorodezki, Julia; Zhang, Michael; Ho, Chelsea; MacCann, Carolyn (Personality and Individual Differences, 2022)
The Dark Triad of socially aversive personality traits (narcissism, Machiavellianism, and psychopathy) may be linked with emotional deficits, including the use of less effective emotion regulation processes. In this meta-analysis, we identify 20 sources (n = 23 samples, k = 83 effect sizes, NTotal = 4487) examining the association of the Dark Triad domains and facets with emotion regulation processes of reappraisal (thought to be effective) and expressive suppression (thought to be ineffective). In line with our hypotheses, we found that both primary and secondary psychopathy were significantly associated with lower use of reappraisal (ρ = −0.18 and − 0.29 respectively, k = 3 to 4), and higher use of expressive suppression (ρ = 0.23 and 0.19 respectively, k = 9 to 10). There were no significant associations of either regulation process with Machiavellianism, total narcissism, or grandiose narcissism. However, vulnerable narcissism was significantly associated with higher use of expressive suppression (ρ = 0.37, k = 2), as hypothesized. Results are discussed in relation to how they may inform our understanding of the emotional deficits of the dark triad, and we emphasise the importance of considering dark personality at the facet rather than the domain level.
No DU affiliation